Trastornos del eje cerebro intestino y psicobióticos: ¿Qué son y cuál es su evidencia? - Higuera, Michelle Carrillo (Revista Gastrohnup)
Disorders of Gut–Brain Interaction are characterized by altered communication between the intestinal microbiota, the enteric nervous system, and the central nervous system. In pediatrics, these disorders such as infant colic, regurgitation, and functional constipation are common and affect both digestive health and emotional well-being. Advances in understanding the microbiota–gut–brain axis have led to the identification of psychobiotics as an emerging therapeutic strategy. These probiotics or prebiotics modulate neurotransmitters, reduce inflammation, and strengthen the intestinal barrier, positively influencing mood and cognitive function. Evidence suggests that psychobiotics act through the vagus nerve, the serotonergic system, and brain-derived neurotrophic factor. Although their safety and tolerability in children are favorable, robust clinical studies are needed to define optimal strains, doses, and treatment duration. The integration of omics tools and personalized medicine strengthens the potential of psychobiotics as preventive and therapeutic interventions in pediatric neurogastroenterology.